2015
DOI: 10.4103/0019-5154.164416
|View full text |Cite
|
Sign up to set email alerts
|

Oral tranexamic acid with fluocinolone-based triple combination cream versus fluocinolone-based triple combination cream alone in melasma: An open labeled randomized comparative trial

Abstract: Background:Melasma is a common acquired cause of facial hyperpigmentation with no definitive therapy. Tranexamic acid, a plasmin inhibitor, has demonstrated depigmenting properties and combining this oral drug with other modalities of treatment has shown promising results.Objectives:To compare the efficacy of a combination of oral tranexamic acid and fluocinolone-based triple combination cream with that of fluocinolone-based triple combination cream alone in melasma among Indian patients.Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Melasma may impose major psychological and emotional burden on patients and affect their quality of life. Common therapeutic approaches for melasma include topical hydroquinone (HQ), azelaic acid, steroids, chemical peels, and lasers, most of which could not induce remarkable and constant satisfying outcomes [2, 3, 7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melasma may impose major psychological and emotional burden on patients and affect their quality of life. Common therapeutic approaches for melasma include topical hydroquinone (HQ), azelaic acid, steroids, chemical peels, and lasers, most of which could not induce remarkable and constant satisfying outcomes [2, 3, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of action of tranexamic acid is still unknown, but the evidence shows that it can reduce the melanin content of epidermis, decrease the dermal vascularity, and mast cell numbers[7]. …”
Section: Introductionmentioning
confidence: 99%
“…Natalia et al 71 combination of oTA with topical therapy utilizing HQ and retinoid products is recommended as a first-line treatment. These studies 42,44,50,52,58,71 suggested that oTA enhanced the efficacy of RTA, and the combination of both resulted in a 1 + 1 ≥ 2 effect due to the effect of both TA and HQ to inhibit melanin formation by melanocytes. It is worth noting that in the ΔMASI results of last follow-up, oTA combined with routine topical agents did not show statistically significant differences from oTA alone.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has also been used for the treatment of melasma. Evidence shows that TXA contributes to the reduction in epidermal melanin content, mast cell numbers, and dermal vascularity 6 ; nevertheless, its precise mechanism of action remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used for the treatment of melasma. Evidence shows that TXA contributes to the reduction in epidermal melanin content, mast cell numbers, and dermal vascularity 6 ; nevertheless, its precise mechanism of action remains unknown. TXA has been applied through different modes of administration, including topically, orally, and intradermally, in the treatment of melasma 7–9 .…”
Section: Introductionmentioning
confidence: 99%